Consumer preferences for Mobility-as-a-Service (MaaS) in Australia. (August 2020) - Vij, Akshay; Ryan, Stacey; Sampson, Spring; Harris, Susan
Highlights: Up to 46 per cent of Australian population willing to adopt MaaS. Consumers prefer pay-as-you-go MaaS schemes to bundled MaaS schemes. Public transport and taxis are the most popular transport services. Willingness to use MaaS is negatively correlated with age and lifecycle stage. Abstract: Mobility-as-a-Service, or MaaS, offers potential consumers access to multiple transport modes and services, owned and operated by different mobility service providers, through an integrated digital platform for planning, booking and payment. We surveyed 3985 geographically and demographically representative Australians nationwide, to understand consumer demand and willingness to pay for MaaS in Australia. Our analysis reveals that there is definitely a market for MaaS in Australia. Depending on the service offering, we find that up to 46 per cent of the Australian population would be willing to adopt MaaS. On average, consumers prefer pay-as-you-go schemes to bundled schemes that offer unlimited access to one or more transport modes and services at fixed monthly costs. Local public transport, taxis and long-distance public transport are the most popular transport services; bikeshare is the least popular. Willingness to use MaaS is strongly correlated with age and lifecycle stage: young individuals who are employed full-time are most likely to use MaaS; older adults who have retired from the workforce and whose children have left home are least likely to use MaaS. Our analysis identifies Melbourne, Canberra and Sydney as good markets for MaaS trials and early launches.